Chinese Patent Medicine Liuweiwuling Tablet had Potent Inhibitory Effects on Both Wild-Type and Entecavir-Resistant Hepatitis B Virus (HBV) in vitro and Effectively Suppressed HBV Replication in Mouse Model - Ge, Fei-lin; Si, Lan-lan; Yang, Yan; Li, Yuan-hua; Lv, Zhong-lin; Liu, Wen-hui; Liao, Hao; Wang, Jun; Zou, Jun; Li, Le; Li, Hui; Zhang, Zi-lin; et al. (Frontiers in Pharmacology, 2021)
Liuweiwuling Tablet (LWWL) is a licensed Chinese patent medicine (approval number: Z20060238) included in the national health insurance for anti-inflammation of chronic HBV infection, whereas its anti-HBV effect remains clarification. The study aimed to clarify its antiviral effect and related mechanisms. HepG2.2.15 cells (wild-type HBV-replicating cells) and HepG2. A64 cells (entecavir-resistant HBV-replicating cells) were used for in vitro test. Hydrodynamic injection-mediated HBV-replicating mouse model was used for in vivo test. Active compounds and related mechanisms for antiviral effect of LWWL were analyzed using network pharmacology and transcriptomics. The inhibition rates of LWWL (0.8 mg/ml) on HBV DNA, HBsAg, and pgRNA were 57.06, 38.55, and 62.49% in HepG2.2.15 cells, and 51.57, 17.57, and 53.88% in HepG2. A64 cells, respectively. LWWL (2 g kg−1 d−1 for 4 weeks)-treated mice had 1.16 log10 IU/mL decrease of serum HBV DNA, and more than 50% decrease of serum HBsAg/HBeAg and hepatic HBsAg/HBcAg. Compared to tenofovir control, LWWL was less effective in suppressing HBV DNA but more effective in suppressing HBV antigens. Thirteen differentially-expressed genes were found in relation to HBV-host interaction and some of them were enriched in interferon (IFN)-β pathway in LWWL-treated HepG2.2.15 cells. CD3+CD4+ T-cell frequency and serum IFN-γ were significantly increased in LWWL-treated mice compared to LWWL-untreated mice. Among 26 compounds with potential anti-HBV effects that were predicted by network pharmacology, four compounds (quercetin, luteolin, wogonin, and kaempferol) were experimentally confirmed to have antiviral potency. In conclusion, LWWL had potent inhibitory effect on both wild-type and entecavir-resistant HBV, which might be associated with increasing IFN-β and IFN-γ production.